Efficacy of retinoids alone or in combination with other remedies in the management of warts: A systematic review and network meta‐analysis. Issue 2 (3rd February 2021) - Salman, Samar; S.A. Shehata, Mohamed; Ibrahim, Ahmed Mohamed; Awad, Mina; Sarsik, Sameh; El‐shirbiny, Hassan; Fathi, Mohamed; Agha, Nadim Yakoub; Anis, Ruba; Abdel Daim, Mohamed M.
Abstract: The use of combined systemic retinoids and intralesional immunotherapy in the management of warts is still debatable without straightforward evidence. Through network meta‐analysis, the current study evaluated the efficacy and safety of systemic retinoids alone or combined with other remedies in the treatment of warts. We searched six literature databases for clinical trials that compared systemic retinoids to local treatments or placebo in wart management. Outcomes were calculated as odds ratios (OR) with 95% confidence‐interval. We used the R software to perform conventional and network meta‐analyses (with a frequentist approach). Network meta‐analysis of eight trials showed that oral acitretin plus intralesional Candida Ag (OR = 367.71), INF‐α plus oral isotretinoin (OR = 223.77), oral acitretin (OR = 117), Candida Ag (OR = 91.93), oral isotretinoin (OR = 62.26) and topical isotretinoin (OR = 17.69) had higher complete recovery rates than placebo. Regarding the P ‐score, oral acitretin plus intralesional Candida Ag had the highest efficacy in achieving complete response ( P ‐score = 0.88), followed by INF‐α plus oral isotretinoin ( P ‐score = 0.79), then oral acitretin ( P ‐score = 0.60). Variable baseline characteristics and lack of data on some outcomes. The current study shows the efficacy for systemic retinoids in the treatment of warts, especially reluctant or recurrent types. Moreover, combinations of systemic retinoids with intralesional immunotherapy yield higher rates of complete clearance with lower recurrence.